The strides to reduce salt intake in Brazil: have we done enough? - Nilson, Eduardo Augusto Fernandes (Cardiovasc Diagn Ther, 2015)
Non-communicable chronic diseases (NCDs) are a major cause of morbidity and mortality in Brazil and inadequate diet is an important risk factor. Among the NCDs, cardiovascular diseases are very prevalent and sodium reduction in the population is a priority of health sector, because Brazilians consume more than twice the daily World Health Organization (WHO) sodium recommendation. Taking into account that sodium sources vary in the country among different age and income groups, several strategies are needed in order to reduce sodium intake, as consumer education, food reformulation, health promotion in school and work settings, food regulation and healthcare initiatives. So far, since 2011, the first results of sodium targets for processed foods and healthcare improvements are promising, and bring lessons that can be helpful for other countries. Nevertheless, more efforts on communication for healthy behaviors, food regulation, engagement of other partners and stakeholders and improving the monitoring system are key to advance in reducing sodium consumption from 4,700 to 2,000 mg per day until 2020.